Biosorpsi Ni2+ oleh Nannochloropsis Salina pada Medium Terpapar Ca2+ - Yusafir Hala; Muhammad Zakir; Emma Suryati; Karuniawati Azis (Jurnal Kimia Valensi, 2015)
Research on biosorption of Ni2+ by N. salina in Ca2+ exposed medium has been done.  This study aimed to determine the growth and efficiency of N. salina towards Ni2+ in Conwy Medium with addition of Ca2+.  Exposure of mixed ions of Ni2+ 5 ppm and Ca2+ with variation of concentrations 10, 30, 50 ppm was conducted at the beginning of the growth of N. salina.  The growth of N. salina was observed every day by counting the number of N. salina population using a microscope and haemocytometer.  The concentration of metal ions after the exposure was determined by atomic absorption spectrophotometer.  The growth of N. salina in medium with exposed metal ions is lower than the control.  The maximum sorption efficiency of Ni2+ as a single ion is 55.2%. After exposure of mixed ions of Ni2+ and Ca2+ with variation of concentrations 10, 30, 50 ppm, the sorption efficiency of Ni2+ in sequents are 17.6%; 17.8%; and 19.6%; while the maximum sorption efficiency of N. salina towards Ca2+ are 5.1%; 7.1%; and 4.0% respectively.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3153